Helping Families Help Themselves? Heterogeneous Effects of a Digital Parenting Program - Amaral, Sofia; Dinarte Diaz, Lelys; Dominguez, Patricio; Perez-Vincent, Santiago M. (World Bank, Washington, DC, 2021)
Parenting practices are crucial for the development of children’s brains and social skills. However, parenting styles may be far from ideal, particularly those of caregivers with high stress levels. Using an individual-level experiment with male and female caregivers of young children in El Salvador, this paper evaluates the impact of a free digital stress management and positive parenting intervention. The results indicate that, for males, the intervention increased stress and anxiety and lowered caregiver-child interactions. The effect on males was concentrated among the poorer and those residing with a partner. In contrast, women’s mental health was not impacted. Yet, their use of physical violence toward children decreased by 18 percent. These results align with theories linking economic deprivation and family structure to caregivers’ cognitive overload and mental health.